2009
DOI: 10.1097/tp.0b013e3181bb48c2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Biliary Complications After Adult Living-Donor Versus Deceased-Donor Liver Transplantation

Abstract: Biliary complications were more frequent after LDLT compared with DDLT. Endoscopic treatment of anastomotic biliary strictures was successful in a minority of patients after LDLT, in contrast with DDLT. Most biliary leaks were successfully treated at endoscopy after LDLT or DDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Some, such as hepatic artery thrombosis, have been identified as a risk factor; some, such as prolonged cold and warm ischemia, have been demonstrated to be associated with biliary complications, and some, such as donor type, are still conflicting. Several studies reported that the use of living donor graft was strongly correlated with biliary complications after transplantation as a result of a small duct size, the presence of multiple duct orifices, and devascularization of the bile duct (5,9,16,20). In the present study, no significant difference in overall biliary complications or the type of biliary complications between LDLT and DDLT recipients was observed.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Some, such as hepatic artery thrombosis, have been identified as a risk factor; some, such as prolonged cold and warm ischemia, have been demonstrated to be associated with biliary complications, and some, such as donor type, are still conflicting. Several studies reported that the use of living donor graft was strongly correlated with biliary complications after transplantation as a result of a small duct size, the presence of multiple duct orifices, and devascularization of the bile duct (5,9,16,20). In the present study, no significant difference in overall biliary complications or the type of biliary complications between LDLT and DDLT recipients was observed.…”
Section: Discussioncontrasting
confidence: 43%
“…Several risk factors include primary underlying disease, type of donor, ABO incompatibility, ischemic time, surgical technique, hepatic artery problems, and rejection for the development of posttransplant biliary complications (4)(5)(6)(7)(8)(9)(10). Several studies previously demonstrated that endoscopic treatment modalities effectively treat the majority of biliary complications following liver transplantation (11)(12)(13)(14)(15)(16)(17)(18). The aims of the present study were to review biliary complications following liver transplantation in a single-center experience to identify the factors associated with the frequency of biliary complications, and to evaluate the success of endoscopic and percutaneous treatment modalities in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, those of LDLT have been reported to occur more frequently: 7.3%-60.0% in right-lobe grafts[ 4 , 12 , 26 - 28 ] and 24% in left lateral segment grafts[ 29 ]. In a study by Gomez et al[ 30 ], biliary strictures occurred more frequently following LDLT than in DDLT [10/30 (33.3%) vs 27/357 (7.6%), respectively].…”
Section: Bile Duct Strictures: Ldlt Vs Ddltmentioning
confidence: 99%
“…Anastomotic biliary stricture was the most common complication associated with liver transplant (Table 5 ). The incidence of biliary stricture is higher in LDLT than in DDLT, 4 , 16 which might be explained by devascularization of the bile duct at the hilar dissection of the graft and the technical challenges of biliary reconstruction (eg, multiple-duct orifice and small ducts). All strictured bile duct cases in our study were successfully treated with endoscopic retrograde biliary drainage or PTBD.…”
Section: Discussionmentioning
confidence: 99%